The impact of the COVID-19 pandemic on the frequency of routine visits and breastfeeding plans on Kasih Medika Clinic - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Firsta Sesarina Mintariani; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; NI Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Ni Komang Anik Pirgantari; Ni Luh Putu Yulia Padmawati; Anak Agung Wahyu Putri Agustini (Indonesian Journal of Perinatology, 2021)
Introduction. The SARS-CoV-2 pandemic has affected every part of the population, including pregnant mothers, breastfeeding mothers, and infants. There is an inadequate comprehension of SARS-CoV-2 transmission potential as of now. As expected, it will result in anxiety among the public, including a specific issue such as breastfeeding practice for the suspected or confirmed novel coronavirus infection. This study aimed to assess whether such anxiety was present in a population of patients that routinely visit Kasih Medika clinic. Methods. This is a simple study conducted on August 5-10, 2020. This study used a questionnaire instrument with samples of pregnant and postpartum mothers. The questionnaire includes a question regarding the anxiety surrounding breastfeeding, visiting the clinic and their everyday activity. Results. We reported that COVID-19 has an impact on the breastfeeding plans from the respondent's questionnaire. All respondents felt anxious about COVID-19, although only 18% of patients reduce their routine visits to Kasih Medika, while the rest keep visiting as scheduled. Eighty-six percent of respondents restricted their outdoor activities during the COVID-19 pandemic. The COVID-19 pandemic causes 27% of the respondents to feel afraid of their breastfeeding plans. However, in the primigravida population, 45.45% of respondents were afraid of their breastfeeding plans. Meanwhile, in the multigravida and postpartum respondents, 90.90% were not afraid about their breastfeeding plans during the COVID-19 period. Conclusion. COVID-19 pandemic brings a certain degree of anxiety to the mothers, including anxiety of safety during breastfeeding practice. Despite the risk of transmission, breastfeeding has more benefits than disadvantages. Breastfeeding makes the infant have a good immune system, which prevents any disease, including COVID-19. Breastfeeding during the COVID-19 is still recommended under health protocol.